Early-life antibiotic exposure aggravate the metabolic dysfunction-associated steatotic liver disease associated hepatocellular carcinoma - Panpan Tian; Xinyu Tian; Lifen Gao; Chunhong Ma; Xiaohong Liang (BMC Cancer)
Abstract Background Metabolic dysfunction-associated steatotic liver disease (MASLD) asscociated hepatocellular carcinoma (HCC) is becoming a growing concern in global healthcare. The early-life gut microbiota plays a crucial role in maintaining healthy. However, the impact of early-life gut microbiota dysbiosis on the advancement of MASLD-HCC remains inadequately understood. Methods In the present study, we investigated the role of early-life gut microbiota in the development of MASLD-HCC in streptozotocin and high-fat diet (STZ-HFD) induced mouse model. We recorded the body weight and lifespan, and dynamically monitored the level of alanine aminotransferase (ALT), aspartate aminotransferase (AST), triglyceride (TG), total cholesterol (T-CHO) and blood glucose in the serum monthly. In addition, we examined various immune cells present in the liver, such as T cells, B cells, NK cells, NKT cells, αβT cells, γδT cells, macrophage and MDSC cells by flow cytometry and conducted liquid chromatography mass spectrometry (LC–MS) based analysis on liver tissue from control and early-life antibiotic exposure mice (early-Abx) MASLD-HCC mice. Results We found that early-Abx mice suffered from more severe tumor burden and further confirmed that hepatocytes and immune cells were all disturbed. Importantly, early-life antibiotic exposure alters the liver metabolic profiling especially glycerophospholipids and lipid accumulation. Furthermore, mice exposed to antibiotics in early-life showed disturbances in glucose metabolism and developed insulin resistance. Conclusions Collectively, our findings revealed that early-life antibiotic exposure accelerated the progression of MASLD-HCC by impairing the hepatocytes, immune homeostasis and metabolites persistently, highlighting the importance of the early-life microbiota in the development of MASLD-HCC.